Dilemmas of Socio-Economic Security of a Modern Family - Waldemar A. KUNZ (Communications of International Proceedings, 2021)
There is no doubt that the family and marriage are the basic unit of society, and its decomposition, to a large extent, lowers the level of social, economic and economic security of the state and the nation, giving rise to various pathologies, including crime and violence, not to mention increased social welfare expenditures for the needy from broken families, which reflects negatively on the state budget - of course, what is at stake is the assumption by institutional entities of particular functions of the family, which is unable to perform its basic functions. The demographic crisis of societies is negatively reflected in the condition of economies and it becomes a seeming necessity to accept immigrants who, in most cases, do not enter the labor market due to their illiteracy, different culture, different system of values and preferred claimant attitudes towards the already overburdened with social welfare obligations. The aim of this article is to show the dilemmas of socio-economic security of the modern family in the face of numerous forces contesting its disintegration.
Keywords: Socio-economic development; security; family.